2014
DOI: 10.1155/2014/815802
|View full text |Cite
|
Sign up to set email alerts
|

MDCT of Small Bowel Obstruction: How Reliable Are Oblique Reformatted Images in Localizing Point of Transition?

Abstract: The goal of this study is to prospectively assess the additional value of oblique reformatted images for localizing POT, having surgery as a reference standard. Materials and Methods. 102 consecutive patients with suspected small bowel obstruction (SBO) underwent 64-slice multidetector row CT (MDCT) using surgical findings as reference standard. Two independent GI radiologists reviewed the CT scans to localize the exact POT by evaluating axial images (data set A) followed by axial, coronal, and oblique MPR ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…He reported that adhesions were seen in 36% of patients of small bowel obstruction found in nine out of 25 patients [12]. In a study by Memon W et al, out of 120 patients, 59 (57.8%) were found to have adhesions, with 19 patients having adhesions at multiple levels [6]. The results of our study are in concordance with the results of these studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…He reported that adhesions were seen in 36% of patients of small bowel obstruction found in nine out of 25 patients [12]. In a study by Memon W et al, out of 120 patients, 59 (57.8%) were found to have adhesions, with 19 patients having adhesions at multiple levels [6]. The results of our study are in concordance with the results of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…It is of immense importance to promptly diagnose the cause of bowel obstruction to prevent severe complications such as ischemia and bowel necrosis [1,6]. The diagnosis of bowel obstruction is made on the basis of history, clinical examination, and radiological findings [7].…”
Section: Introductionmentioning
confidence: 99%
“…For evaluating whether SBO was present and obstruction severity, there were no differences among the three protocols with respect to diagnostic self-confidence, agreement, detection rate, and accuracy. These results are consistent with previous findings[5,6,13,14,19,20] and suggest that the conventional axial and coronal reformations may be sufficient to evaluate whether SBO is present and the obstruction severity without the need for additional post-processing techniques.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is the first to integrate and optimize the MDCT multiple post-processing techniques to develop a more accurate post-processing protocol for SBO assessment. The protocols mainly used MPR and CPR to show the obstruction site and its connected proximal and distal bowel segments[13,14,17-20]. MIP and VR were mainly used to reveal local mesenteric changes and mesenteric vascular diseases, as well as the obstruction site.…”
Section: Discussionmentioning
confidence: 99%
“…Common factors include inflammation, sympathetic nerve inhibition, release of neurotransmitters, hormones, and the use of narcotic drugs, analgesic drugs, etc. [22][23][24]. Inflammation can cause intestinal edema and hyperemia in patients, leading to intestinal adhesions and formation of intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%